Scientific opinion on toxicity of pyrethroid common metabolites. (21st October 2022) - ,; Hernandez‐Jerez, Antonio F; Adriaanse, Paulien; Aldrich, Annette; Berny, Philippe; Duquesne, Sabine; Focks, Andreas; Marinovich, Marina; Millet, Maurice; Pelkonen, Olavi; Pieper, Silvia; Tiktak, Aaldrik; et al.
Abstract: The EFSA Panel on Plant Protection Products and their Residues was requested by the European Commission, to conclude based upon available evidence if metabolites 3‐phenoxybenzoic acid (PBA) and 3‐(4′‐hydroxyphenoxy)benzoic acid (PBA(OH)), common to several pyrethroid compounds, have genotoxic properties, if they share the (neuro)toxicity profile of their parent compounds, and if evidence allows to conclude on their health‐based guidance values. Available body of evidence consisted of studies from regulatory dossiers submissions, as well as from public literature. In addition, the data gap for short‐term toxicity profile of PBA was addressed by read‐across. Assessment revealed that PBA and PBA(OH) do not raise a concern with respect to genotoxicity. As regards general toxicity, PBA and PBA(OH) have different qualitative (no neurotoxic mechanism) and quantitative (higher NOAELs) toxicity compared to the parent pyrethroid compounds. For both metabolites, acceptable daily intake (ADI) and acute reference dose (ARfD) values were derived at 0.1 mg/kg body weight (bw) per day and 1 mg/kg bw, respectively.